PENGARUH METODE PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) BERBANTUAN MEDIA MINI WHITEBOARD TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 3 PENGADANGAN - M.Pd, Muh.Yazid,; Khatimah, Husnul; M.Pd, M. Deni Siregar,; M.Pd, Atiaturrahmaniah, (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the cooperative learning method Type Think Pair Share (TPS) assisted by mini whiteboard media on the mathematics learning outcomes of fourth grade students at SD Negeri 3 Pengadangan in fraction material. The research method used in this study is quantitative with a quasi-experimental research type using a one group pretest-posttest design. The study was conducted at SD Negeri 3 Pengadangan with a sample of 20 fourth grade students. Data collection techniques were carried out through learning outcome tests and documentation. Data analysis used the Shapiro-Wilk normality test and hypothesis testing using the Paired Sample t-Test. The results showed that the students’ average pretest score was 61.90 and increased in the posttest to 85.10. The normality test showed that the data were normally distributed. The results of the Paired Sample t-Test obtained a significance value of 0.000 < 0.05 so H₁ was accepted and H₀ was rejected. This indicates that there is a significant effect of the cooperative learning method Type Think Pair Share (TPS) assisted by mini whiteboard media on students’ mathematics learning outcomes.